1987
DOI: 10.1002/1097-0142(19870115)59:2<310::aid-cncr2820590224>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma with sarcomatous change. Clinicopathologic and immunohistochemical studies of 14 autopsy cases

Abstract: Among 355 autopsy cases of hepatocellular carcinoma (HCC), 14 cases exhibited sarcomatous appearance (incidence, 3.9%). A clinicopathologic study was performed in these 14 cases, and the immunohistochemical localization of keratin (KRT), vimentin (VMT), albumin (ALB), fibrinogen (FBG) and alpha-fetoprotein (AFP) was also examined using the avidin-biotin complex method. Clinically, the HCCs with sarcomatous appearance were characterized by negative or low serum AFP levels and high incidence of extrahepatic meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(102 citation statements)
references
References 19 publications
6
96
0
Order By: Relevance
“…18) Sarcomatous change in the liver is considered as a result of dedifferentiation. 19,20) In fact, we found that a small number of these sarcomatoid CC cells showed spontaneous morphologic and phenotypic transformation into a maturer stage in continuous culture. In order to clarify the mechanism of these changes, we examined the response of the sarcomatoid cells to some possible cytokines.…”
supporting
confidence: 65%
“…18) Sarcomatous change in the liver is considered as a result of dedifferentiation. 19,20) In fact, we found that a small number of these sarcomatoid CC cells showed spontaneous morphologic and phenotypic transformation into a maturer stage in continuous culture. In order to clarify the mechanism of these changes, we examined the response of the sarcomatoid cells to some possible cytokines.…”
supporting
confidence: 65%
“…The remaining 13 had non-cirrhotic HCC tumours. A further two patients had sarcomatoid transformation of hepatocellular carcinoma (Kakizoe et al, 1987). The study included 14 women and 28 men with a mean age of 54.6 years (range 14-73 years).…”
Section: Methodsmentioning
confidence: 67%
“…In contrast to the relatively high frequency of HCC, the incidence of sarcomatous change involved is relatively low and reportedly 3.9% among 350 HCC cases at autopsy [10]. However, the incidence of HCCSC is apparently increasing, reasons for which include the reported increase frequency of transarterial chemotherapy and/or embolization of HCC [11].…”
Section: Discussionmentioning
confidence: 99%